2018
DOI: 10.1139/cjm-2017-0752
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the rhizosphere bacterial community across different cultivation years in saline–alkaline paddy soils of Songnen Plain of China

Abstract: The characteristics of the rhizosphere microbial community across different cultivation years (from 1, 3, 5, 15, 20, and 50 years) in saline-alkaline paddy soils in Songnen Plain of China were investigated based on sequence variation of 16S rDNA using Illumina MiSeq sequencing. The results showed that the microbial community diversity varied across cultivation years, showing higher diversity in cultivation years >15 than in cultivation years <15. The dominant microbial community of the rhizosphere was mainly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…The proportion of Acidobacteria Gp6 increased in all treatments by the end of the year, and the highest abundance was observed in NS in October. A previous study showed that Acidobacteria Gp6 was negatively related to pH under saline-alkaline conditions (Cui et al, 2018), which was confirmed in our study. Therefore, the abundance of Acidobacteria Gp6 was relatively low under fallow conditions with manure (MS and MM).…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of Acidobacteria Gp6 increased in all treatments by the end of the year, and the highest abundance was observed in NS in October. A previous study showed that Acidobacteria Gp6 was negatively related to pH under saline-alkaline conditions (Cui et al, 2018), which was confirmed in our study. Therefore, the abundance of Acidobacteria Gp6 was relatively low under fallow conditions with manure (MS and MM).…”
Section: Discussionsupporting
confidence: 91%
“…However, the potential role of seed-associated bacteria on seed germination under salt stress are poorly characterized. Some beneficial microbes in the rhizosphere bacterial community possess diverse metabolic capabilities and play crucial roles in plant adaptation to environmental stresses [24][25][26][27]. Thus, we hypothesize that spermosphere bacterial communities may also have implications for seed germination and survival under salt stress, which requires in-depth study.…”
Section: Introductionmentioning
confidence: 96%
“…Under the salt-affected environment, soil microbial community composition was found to respond well to the interactive effect of amendment measures, including biochar-manure compost (Lu et al, 2015), biogas residue (Shi, Liang, Leng, Wang, & Wang, 2018), flue-gas desulfurization gypsum by-products (Li et al, 2012), saline water irrigation (Chen et al, 2017) and even duration of cultivation (Cui et al, 2018).…”
Section: Introductionmentioning
confidence: 99%